2018
DOI: 10.1002/anie.201812754
|View full text |Cite
|
Sign up to set email alerts
|

The Barrier to Proton Transfer in the Dimer of Formic Acid: A Pure Rotational Study

Abstract: The rotational spectra of three C-deuterated isotopologues of the dimer of formic acid have been measured, thanks to the small dipole moment induced by asymmetric H! Ds ubstitution(s). Fort he DCOOH-HCOOH species,t he concerted double proton transfer of the two hydroxy hydrogen atoms takes place between two equivalent minima and generates at unneling splitting of 331.2(6) MHz. This splitting can be reproduced by a3Dmodel with abarrier of 2559 cm À1 (30.6 kJ mol À1 )aso btained from theoretical calculations.Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 51 publications
8
61
0
Order By: Relevance
“…[7,8] In particular,j et-cooled Fouriert ransform microwave (FTMW) spectroscopy has been demonstrated as one of the most sensitive and powerful techniques with which to obtain precise information about the structure and dynamics of molecular complexes. [9][10][11] For example, FTMW spectroscopy was utilized in the recent analysiso ft he formic acid dimer, [11] among alarge list of acid-acid heterodimers. [12][13][14][15][16][17][18][19][20] Some of the reportedw ork focuses on proton transfer, [13][14][15][16] which is relatedt og eneticm utations of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] In particular,j et-cooled Fouriert ransform microwave (FTMW) spectroscopy has been demonstrated as one of the most sensitive and powerful techniques with which to obtain precise information about the structure and dynamics of molecular complexes. [9][10][11] For example, FTMW spectroscopy was utilized in the recent analysiso ft he formic acid dimer, [11] among alarge list of acid-acid heterodimers. [12][13][14][15][16][17][18][19][20] Some of the reportedw ork focuses on proton transfer, [13][14][15][16] which is relatedt og eneticm utations of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The parametrization used here was adapted to yield the correct infrared spectrum in the gas phase [185]. Recent high-resolution work has confirmed that the barrier of 7.3 kcal mol −1 for the gas-phase PES is compatible with the tunneling splitting observed in microwave studies [186]. Such a barrier height makes spontaneous transitions rare.…”
Section: Outlook and Conclusionmentioning
confidence: 87%
“…However, the H!Da symmetric substitution generates at iny dipole moment, which allowed the observation of the tunneling due to the concerted double proton transfer. [56] Trimers andt etramers have been observed by Xu et al on mono- [57] and trifluorinated [58] ethanol,s tabilized by ac ombination of hydroxyl Figure 4. A) Antigeared and B) gearedi nstanton tunneling pathways [51] in the water hexamer prism,t ogether with C) the variation of the potential energy along the instanton paths.…”
Section: Self-aggregation and Oligomer Formationmentioning
confidence: 90%
“…The dimer should not be observable because of a lack of a permanent dipole moment. However, the H→D asymmetric substitution generates a tiny dipole moment, which allowed the observation of the tunneling due to the concerted double proton transfer . Trimers and tetramers have been observed by Xu et al.…”
Section: Self‐aggregation and Oligomer Formationmentioning
confidence: 97%